ELE8311 - Module 2 - The Z-Transform
ELE8311 - Module 2 - The Z-Transform
ELE8311 - Module 2 - The Z-Transform
Suppose 𝑦𝑦(𝑘𝑘) is a discrete-time signal, where the independent variable (𝑘𝑘), usually time, is
assumed to have a discrete set of possible values, then a difference equation can be used to
represent the system shown in Fig.2.1 as in (2.1).
where, 𝑢𝑢(𝑘𝑘) = 𝑢𝑢(𝑘𝑘𝑘𝑘), 𝑘𝑘 = 0,1,2, … is an input sequence (also called a forcing function), and
𝑦𝑦(𝑘𝑘) = 𝑦𝑦(𝑘𝑘𝑘𝑘) is an output sequence (also called the response). A difference equation, such
as (2.1), is said to be of order 𝑛𝑛 because the difference between the highest and lowest time
arguments of 𝑦𝑦(. ) and 𝑢𝑢(. ) is 𝑛𝑛 . If the coefficients 𝑎𝑎𝑖𝑖 , 𝑏𝑏𝑖𝑖 | 𝑖𝑖 = 0, 1, 2, …, are constant, the
difference equation is referred to as linear time invariant (LTI). If the forcing function 𝑢𝑢(𝑘𝑘) is
equal to zero, the equation is said to be homogeneous.
1
ELE8311: The z-Transform
Example: Determine the order of the following difference equations. Identify whether the
equation is: (i) linear, (ii) time invariant, or (iii) homogenous.
Solution:
(a) The equation is second order. All terms are linear with constant coefficients, thus it is
LTI. There is a forcing function in the equation, thus, it is non-homogeneous.
(b) The difference equation is fourth order. The second coefficient is time dependent, but
all terms are linear. It is therefore a linear time varying, homogeneous equation.
(c) This is a first order difference equation with a nonlinear term at the right hand side. It
has no forcing function. The equation is therefore nonlinear, time invariant, and
homogeneous.
Example:
Consider the LTI difference equation (2.2), find its response due to the initial conditions
𝑦𝑦(−2) = 1, 𝑦𝑦(−1) = 2 under a unit step input sequence 𝑢𝑢(𝑘𝑘) = 1, for = 0,1,2, … .
Solution:
1
𝑦𝑦(𝑘𝑘) = [−2𝑦𝑦(𝑘𝑘 − 1) + 𝑦𝑦(𝑘𝑘 − 2) + 2𝑢𝑢(𝑘𝑘 − 1) − 3𝑢𝑢(𝑘𝑘 − 2)]
3
Then, the response for the given initial conditions and forcing function is obtained recursively
as follows:
1 5
𝑦𝑦(0) = [−2𝑦𝑦(−1) + 𝑦𝑦(−2) + 2𝑢𝑢(−1) − 3𝑢𝑢(−2)] =
3 3
1 10
𝑦𝑦(1) = [−2𝑦𝑦(0) + 𝑦𝑦(−1) + 2𝑢𝑢(0) − 3𝑢𝑢(−1)] = −
3 9
1 26
𝑦𝑦(2) = [−2𝑦𝑦(1) + 𝑦𝑦(0) + 2𝑢𝑢(1) − 3𝑢𝑢(0)] =
3 27
2
ELE8311: The z-Transform
Note that this course will focus on LTI difference equations and the z-transform is a
convenient approach for solving LTI problems.
2.2 z-Transform
z-transform is a vital tool for analysis and deisgn of discrete-time systems. Similar to the
Laplace transforms in continuous domain, z-transform converts LTI difference equations to
algebraic equations and convolutions to multiplications.
Def. 2.1:
For a causal signal (𝑘𝑘 ≥ 0) defined by the sequence 𝑓𝑓(𝑘𝑘) = {𝑢𝑢0 , 𝑢𝑢1 , 𝑢𝑢2 , … , 𝑢𝑢𝑘𝑘 , … } , the z-
transform is defined as in (2.2):
∞
where, 𝑧𝑧 −𝑖𝑖 indicates the 𝑖𝑖th sampling instant. Thus, 𝑧𝑧 0 corresponds to the initial time 𝑘𝑘 = 0;
𝑧𝑧 −1 indicates the time instant at 𝑘𝑘 = 1. Hence, 𝑧𝑧 −1 is called the unit-delay element.
Def. 2.2:
Alternatively, the z-transform of a given function can be obtained from its Laplace transforms
as follows.
∞
∗ (𝑠𝑠) −𝑠𝑠𝑠𝑠 −2𝑠𝑠𝑠𝑠 −𝑘𝑘𝑘𝑘𝑘𝑘
𝑈𝑈 = 𝑢𝑢0 + 𝑢𝑢1 𝑒𝑒 + 𝑢𝑢2 𝑒𝑒 + ⋯ + 𝑢𝑢𝑘𝑘 𝑒𝑒 + ⋯ = � 𝑢𝑢𝑘𝑘 (𝑒𝑒 −𝑠𝑠𝑠𝑠 )𝑘𝑘 ,
𝑘𝑘=0
The commonly used excitation signals include discrete-time impulse, sampled step,
exponential and sinusoidal signals. The following identities are essential.
Useful identities:
𝑛𝑛
1 − 𝑎𝑎𝑛𝑛 +1
� 𝑎𝑎𝑘𝑘 = ; 𝑎𝑎 ≠ 1
1 − 𝑎𝑎
𝑘𝑘=0
∞
1
� 𝑎𝑎𝑘𝑘 = ; |𝑎𝑎| < 1
1 − 𝑎𝑎
𝑘𝑘=0
1, 𝑘𝑘 = 0
𝑢𝑢(𝑘𝑘) = 𝛿𝛿(𝑘𝑘) = �
0, 𝑘𝑘 ≠ 0
𝑧𝑧[𝑢𝑢(𝑘𝑘)] = 𝑈𝑈(𝑧𝑧) = 1.
4
ELE8311: The z-Transform
∞
−1 −2 −3 −𝑘𝑘
𝑈𝑈(𝑧𝑧) = 1 + 𝑧𝑧 + 𝑧𝑧 + 𝑧𝑧 + ⋯ + 𝑧𝑧 + ⋯ = � 𝑧𝑧 −𝑘𝑘 .
𝑘𝑘=0
1 𝑧𝑧
𝑈𝑈(𝑧𝑧) = −1
=
1 − 𝑧𝑧 𝑧𝑧 − 1
c. Exponential Signal
𝑎𝑎𝑘𝑘 , 𝑘𝑘 ≥ 0
𝑢𝑢(𝑘𝑘) = �
0, 𝑘𝑘 < 0
Then,
1 𝑧𝑧
𝑈𝑈(𝑧𝑧) = = .
1 − 𝑎𝑎𝑧𝑧 −1 𝑧𝑧 − 𝑎𝑎
5
ELE8311: The z-Transform
z-Transforms – summary
6
ELE8311: The z-Transform
a. Convergence of z-transform
The existence of a unique z-transform depends on the availability of its region of absolute
convergence. Recall that for an impulse signal 𝛿𝛿(𝑛𝑛), let:
7
ELE8311: The z-Transform
Therefore,
1 𝑧𝑧
𝑈𝑈2 (𝑧𝑧) = 1 − =
1 − 𝑎𝑎−1 𝑧𝑧 𝑧𝑧 − 𝑎𝑎
Notice that, although the two sequences 𝑢𝑢1 and 𝑢𝑢2 yield the same z-transform, the
conditions upon which their regions of convergence exist are completely different. Since z-
transform are defined in terms of polynomials in z, which can be real or complex, the
complete definition for case 1 and 2 are as follows:
𝑧𝑧
𝑢𝑢1 (𝑛𝑛) ↔ , |𝑎𝑎𝑧𝑧 −1 | < 1 𝑜𝑜𝑜𝑜 |𝑧𝑧| > |𝑎𝑎|
𝑧𝑧 − 𝑎𝑎
𝑧𝑧
𝑢𝑢2 (𝑛𝑛) ↔ , |𝑎𝑎−1 𝑧𝑧| < 1 𝑜𝑜𝑜𝑜 |𝑧𝑧| < |𝑎𝑎|
𝑧𝑧 − 𝑎𝑎
Fig. 2.4: Region of Convergence of 𝑢𝑢1 (𝑛𝑛) (left) and 𝑢𝑢2 (𝑛𝑛) (right).
8
ELE8311: The z-Transform
Example 2.1:
1 𝑘𝑘 1 𝑘𝑘
𝑢𝑢(𝑘𝑘) = � � 1(𝑘𝑘) + � � 1(𝑘𝑘)
2 3
∞ ∞
1 𝑘𝑘 1 𝑘𝑘
= � � � 1(𝑘𝑘)𝑧𝑧 + � � � 1(𝑘𝑘)𝑧𝑧 −𝑘𝑘
−𝑘𝑘
2 3
𝑘𝑘=−∞ 𝑘𝑘=−∞
∞ ∞
1 𝑘𝑘 −𝑘𝑘 1 𝑘𝑘 −𝑘𝑘
= � � � 𝑧𝑧 + � � � 𝑧𝑧
2 3
𝑘𝑘=0 𝑘𝑘=0
Notice that both regions of convergence intersect. Thus, at |𝑧𝑧| > 1/2 both sums converge
(i.e., their z-transform exist).
Example 2.2:
∞ 0
For the first term, the z-transform is 𝑧𝑧/(𝑧𝑧 − 1) for |𝑧𝑧| > 1. For the second term, however, we
have 0.5/(0.5 − 𝑧𝑧) for |𝑧𝑧| < 0.5.
Now, since the regions of convergence for the first and second term (|𝑧𝑧| > 1 and |𝑧𝑧| < 0.5)
do not intersect (are mutually exclusive), the z-transform of this example does not exist (no
convergence).
Note that we are only interested on signals which have their z-transform defined.
b. Linearity
2𝑧𝑧 6𝑧𝑧 − 4
𝑍𝑍[𝑓𝑓(𝑘𝑘)] = 𝐹𝐹(𝑧𝑧) = 2𝑍𝑍[1(𝑘𝑘)] + 4𝑍𝑍[𝛿𝛿(𝑘𝑘)] = +4=
𝑧𝑧 − 1 𝑧𝑧 − 1
c. Time Delay
This also follows from the time delay property of the Laplace transform:
Example 2.3
4, 𝑘𝑘 = 2,3, …
𝑓𝑓(𝑘𝑘) = �
0, otherwise
This is a sequence that is delayed to start at 𝑘𝑘 = 2 rather than 𝑘𝑘 = 0 . Using the delay
property above:
4𝑧𝑧 4
𝐹𝐹(𝑧𝑧) = 𝑧𝑧{4 × 1(𝑘𝑘 − 2)} = 4𝑧𝑧 −2 𝑧𝑧{1(𝑘𝑘)} = 𝑧𝑧 −2 =
𝑧𝑧 − 1 𝑧𝑧(𝑧𝑧 − 1)
10
ELE8311: The z-Transform
Example 2.4:
Solution:
∞ ∞ ∞
−𝑘𝑘 −𝑘𝑘
𝑧𝑧[𝑢𝑢(𝑘𝑘)] = 𝑈𝑈(𝑧𝑧) = 2 � 𝛿𝛿(𝑘𝑘)𝑧𝑧 − 3 � 𝛿𝛿(𝑘𝑘 − 2)𝑧𝑧 + 4 � 𝛿𝛿(𝑘𝑘 − 5)𝑧𝑧 −𝑘𝑘
𝑘𝑘=−∞ 𝑘𝑘=−∞ 𝑘𝑘=−∞
2𝑧𝑧 5 − 3𝑧𝑧 3 + 4
= 2 − 3𝑧𝑧 −2 + 4𝑧𝑧 −5 = ; |𝑧𝑧| > 0
𝑧𝑧 5
Example 2.5
Therefore,
6𝑧𝑧 2 + 2𝑧𝑧
𝑈𝑈(𝑧𝑧) = ; |𝑧𝑧| > 3
(𝑧𝑧 − 1)(𝑧𝑧 + 3)
d. Time Advance
Example 2.6:
{𝑓𝑓(𝑘𝑘)} = {4,8,16, … }
Solution:
𝑧𝑧 4𝑧𝑧
𝐹𝐹(𝑧𝑧) = 𝑧𝑧 2 𝐺𝐺(𝑧𝑧) − 𝑧𝑧 2 𝑔𝑔(0) − 𝑧𝑧𝑧𝑧(1) = 𝑧𝑧 2 − 𝑧𝑧 2 − 2𝑧𝑧 =
𝑧𝑧 − 2 𝑧𝑧 − 2
Notice that, the solution can also be obtained by rewriting the sequence as:
{𝑓𝑓(𝑘𝑘)} = 4{1,2,4, … }
4𝑧𝑧
𝑧𝑧 − 2
e. Multiplication by Exponent
Example 2.7:
Find the z-transform of cos 𝑤𝑤𝑤𝑤 1(𝑘𝑘) and sin 𝑤𝑤𝑤𝑤 1(𝑘𝑘).
Solution: Using Euler’s identity, it is convenient to benefit from the simplicity of sequences of
the form 𝑎𝑎𝑘𝑘 .
𝑧𝑧
= ; |𝑧𝑧| > �𝑒𝑒 𝑗𝑗𝑗𝑗 � = 1
𝑧𝑧 − 𝑒𝑒 𝑗𝑗𝑗𝑗
𝑧𝑧�𝑧𝑧 − 𝑒𝑒 −𝑗𝑗𝑗𝑗 �
=
(𝑧𝑧 − 𝑒𝑒 𝑗𝑗𝑗𝑗 )(𝑧𝑧 − 𝑒𝑒 −𝑗𝑗𝑗𝑗 )
12
ELE8311: The z-Transform
Fig. 2.4: Poles and Zeros of cos 𝑤𝑤𝑤𝑤 1(𝑘𝑘) (left) and sin 𝑤𝑤𝑤𝑤 1(𝑘𝑘) (right).
𝑧𝑧 sin 𝑤𝑤
(sin 𝑤𝑤𝑤𝑤)1(𝑘𝑘) ↔
(𝑧𝑧 − 𝑒𝑒 𝑗𝑗𝑗𝑗 )(𝑧𝑧
− 𝑒𝑒 −𝑗𝑗𝑗𝑗 )
f. Effect of Damping
The presence of an exponential in time sequence results in the following expression for its z-
transform:
13
ELE8311: The z-Transform
If the limit exists, the z-transform definition of the initial value of a causal signal is obtained
as:
Similarly, if the limit exists, the final value of causal signals is defined as:
𝑧𝑧 − 1
lim 𝑢𝑢(𝑘𝑘) = lim(1 − 𝑧𝑧 −1 )𝑈𝑈(𝑧𝑧) = lim 𝑈𝑈(𝑧𝑧)
𝑘𝑘→∞ 𝑧𝑧→1 𝑧𝑧→1 𝑧𝑧
The above is true if 𝑈𝑈(𝑧𝑧) converges for all |𝑧𝑧| > 1 and if all poles of 𝑈𝑈(𝑧𝑧)(𝑧𝑧 − 1) are inside
the unit circle. The only possible pole of 𝑈𝑈(𝑧𝑧) not strictly inside the unit circle is a simple pole
at 𝑧𝑧 = 𝑎𝑎, which is removed in (𝑧𝑧 − 1)𝑈𝑈(𝑧𝑧).
Example 2.8:
Using the final value theorem, calculate the steady state value of (0.5𝑘𝑘 − 0.5)1(𝑘𝑘). Verify that
this agrees with the direct result.
Solution
𝑧𝑧 0.5𝑧𝑧
(0.5𝑘𝑘 − 0.5)1(𝑘𝑘) ↔ − , |𝑧𝑧| > 1.
𝑧𝑧 − 0.5 𝑧𝑧 − 1
𝑧𝑧 0.5𝑧𝑧
lim � − � (𝑧𝑧 − 1)/𝑧𝑧 → −0.5.
𝑧𝑧→1 𝑧𝑧 − 0.5 𝑧𝑧 − 1
14
ELE8311: The z-Transform
Example 2.9
Does the final value theorem applies to this sequence 2𝑘𝑘 1(𝑘𝑘)?
Solution:
𝑧𝑧
2𝑘𝑘 1(𝑘𝑘) ↔ , |𝑧𝑧| > 2
𝑧𝑧 − 2
Notice that, from the LHS, as 𝑘𝑘 → ∞ we have a growing sequence. Also, from the RHS, we
have:
𝑧𝑧
lim (𝑧𝑧 − 1)/𝑧𝑧
𝑧𝑧→1 𝑧𝑧 − 2
Thus, since the RHS is valid only for |𝑧𝑧| > 2, the theorem cannot even be applied. Hence, the
final value for causal signals cannot be found for growing sequences.
Example 2.10
Find the initial value and final value of a causal sequence whose z-transform is given by:
0.792𝑧𝑧 2
𝑈𝑈(𝑧𝑧) = .
(𝑧𝑧 − 1)(𝑧𝑧 2 − 0.416𝑧𝑧 + 0.208)
Solution
0.792𝑧𝑧 2
lim 𝑈𝑈(𝑧𝑧) = = 0.
𝑧𝑧→∞ 𝑧𝑧 3
0.792
lim(𝑧𝑧 − 1)𝑈𝑈(𝑧𝑧) = = 1.
𝑧𝑧→1 1 − 0.416 + 0.208
Exercise: Verify the above initial and final values by expanding the expression for 𝑈𝑈(𝑧𝑧) by
long division.
15
ELE8311: The z-Transform
h. Convolution
If 𝑈𝑈(𝑧𝑧) and 𝐺𝐺(𝑧𝑧) are z-transforms of {𝑢𝑢(𝑛𝑛)} and {𝑔𝑔(𝑛𝑛)}, respectively, then 𝑈𝑈(𝑧𝑧)𝐺𝐺(𝑧𝑧) is the z-
transform of {𝑢𝑢(𝑛𝑛)} ∗ {𝑔𝑔(𝑛𝑛)}.
∴ 𝑌𝑌(𝑧𝑧) = 𝐺𝐺(𝑧𝑧)𝑈𝑈(𝑧𝑧).
∞ ∞
−𝑘𝑘
= � 𝑔𝑔(𝑘𝑘)𝑧𝑧 � 𝑢𝑢(𝑛𝑛 − 𝑘𝑘)𝑧𝑧 −(𝑛𝑛−𝑘𝑘) ,
𝑘𝑘=0 𝑛𝑛=0
16
ELE8311: The z-Transform
Example 2.11
Determine the step response of a system with impulse response is 𝑔𝑔(𝑛𝑛) = 0.5𝑛𝑛 1(𝑛𝑛).
Solution
Using the z-transform approach, we simply multiply the signal 𝑢𝑢 and the step input 𝑔𝑔 as
follows:
∞ ∞
−𝑗𝑗
1
𝑈𝑈(𝑧𝑧) = � 𝑢𝑢(𝑗𝑗)𝑧𝑧 = � 0.5𝑗𝑗 𝑧𝑧 −𝑗𝑗 = , |𝑧𝑧| > 0.5
1 − 0.5𝑧𝑧 −1
𝑗𝑗 =−∞ 𝑗𝑗 =0
We also have,
∞ ∞
−𝑗𝑗
1
𝐺𝐺(𝑧𝑧) = � 𝑔𝑔(𝑗𝑗)𝑧𝑧 = � 𝑧𝑧 −𝑗𝑗 = , |𝑧𝑧| > 1
1 − 𝑧𝑧 −1
𝑗𝑗 =−∞ 𝑗𝑗 =0
On multiplying, we have:
1 1
𝑌𝑌(𝑧𝑧) = 𝐺𝐺(𝑧𝑧)𝑈𝑈(𝑧𝑧) = , |𝑧𝑧| > 1.
1 − 0.5𝑧𝑧 1 − 𝑧𝑧 −1
−1
i. Complex Differentiation
𝑚𝑚
𝑑𝑑 𝑚𝑚
𝑧𝑧{𝑘𝑘 𝑓𝑓(𝑘𝑘)} = �−𝑧𝑧 � 𝐹𝐹(𝑧𝑧)
𝑑𝑑𝑑𝑑
Example 2.12
Solution
𝑑𝑑 𝑧𝑧 (−𝑧𝑧)�(𝑧𝑧 − 1) − 𝑧𝑧� 𝑧𝑧
𝑧𝑧{𝑘𝑘 × 1} = �−𝑧𝑧 �� �= =
𝑑𝑑𝑑𝑑 𝑧𝑧 − 1 (𝑧𝑧 − 1) 2 (𝑧𝑧 − 1)2
18
ELE8311: The z-Transform
19